1978
DOI: 10.1111/j.1365-2265.1978.tb02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic Hormone in Bronchogenic Carcinoma

Abstract: Immunoactive antidiuretic hormone (ADH) was measured by radioimmunoassay in the plasma, lung tumours and metastatic tumours of nineteen patients with bronchogenic carcinoma. Ten patients had hyponatraemia and carcinoma of the small oat cell type. Plasma ADH measured in nine of these patients ranged from 11--270 pg/ml and was elevated above the normal range (4.6--6.2 pg/ml) in all subjects. ADH-immunoreactive material was detectable in all primary lung tumours (range 9--1080 pg/mg wet weight, n = 7) and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…Patients with bronchogenic carcinoma and hyponatraemia have a higher level of plasma arginine vasopressin (AVP) (Morton et al . ). Other studies have shown that 10–15% of patients with small cell lung cancer have hyponatraemia and that 70% of those patients have elevated plasma AVP (Odell & Wolfsen ; List et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with bronchogenic carcinoma and hyponatraemia have a higher level of plasma arginine vasopressin (AVP) (Morton et al . ). Other studies have shown that 10–15% of patients with small cell lung cancer have hyponatraemia and that 70% of those patients have elevated plasma AVP (Odell & Wolfsen ; List et al .…”
Section: Discussionmentioning
confidence: 97%
“…Again, the higher incidence of SIADH in patients with lung cancer (especially small cell subtype) is the common cause of hyponatraemia in this subtype of cancer (Berghmans et al 2000;Doshi et al 2012). Patients with bronchogenic carcinoma and hyponatraemia have a higher level of plasma arginine vasopressin (AVP) (Morton et al 1978). Other studies have shown that 10-15% of patients with small cell lung cancer have hyponatraemia and that 70% of those patients have elevated plasma AVP (Odell & Wolfsen 1978;List et al 1986;Shapiro & Richardson 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Our data do not indicate that chromogranin-A is a useful marker in the diagnosis of SCLA. (SIADH) are noted to be associated with such ectopic hormone production [105]. The SCLA may also be associated with the carcinoid syndrome resulting in the urinary excretion of excessive amounts of 5-hydroxyindole acidic acid (5-HIAA) or 5-hydroxytryptophan (5-HTP) .…”
Section: Immunohistochemical Studiesmentioning
confidence: 98%
“…They postulated that the tumors led to the inappropriate release of ADH, later discovered to consist of AVP. This suggestion was later confirmed since immunoactive AVP has been noted to be elevated in plasma of patients with bronchogenic carcinoma, 24 as well as in patients with a cancer of the digestive tract. 25 Some tumors may actually demonstrate multiple hormone production and clinical and laboratory evidence of both the ectopic adrenocorticotropic hormone and ADH syndromes.…”
Section: Paraneoplastic Production Of Adhmentioning
confidence: 52%